2014
DOI: 10.1111/tra.12194
|View full text |Cite
|
Sign up to set email alerts
|

AP‐1A Controls Secretory Granule Biogenesis and Trafficking of Membrane Secretory Granule Proteins

Abstract: The adaptor protein 1A complex (AP-1A) transports cargo between the trans-Golgi network (TGN) and endosomes. In professional secretory cells, AP-1A also retrieves material from immature secretory granules (SGs). The role of AP-1A in SG biogenesis was explored using AtT-20 corticotrope tumor cells expressing reduced levels of the AP-1A μ1A subunit. A two-fold reduction in μ1A resulted in a decrease in TGN cisternae and immature SGs and the appearance of regulated secretory pathway components in non-condensing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 94 publications
(131 reference statements)
3
49
0
Order By: Relevance
“…4). As in our previous study (7), the ␥ 3 MSH antibody detected similar amounts of differentially glycosylated POMC and 16-kDa fragment in lysates of Scr and sh-1A PAM-1 cells; consistent with previous metabolic labeling experiments, ABI and 18-kDa fragment were barely detectable in cell lysates (Fig. 4A).…”
Section: Atp7a Ap-1 and Pam Co-localize In The Golgi Region Of Att-supporting
confidence: 92%
See 4 more Smart Citations
“…4). As in our previous study (7), the ␥ 3 MSH antibody detected similar amounts of differentially glycosylated POMC and 16-kDa fragment in lysates of Scr and sh-1A PAM-1 cells; consistent with previous metabolic labeling experiments, ABI and 18-kDa fragment were barely detectable in cell lysates (Fig. 4A).…”
Section: Atp7a Ap-1 and Pam Co-localize In The Golgi Region Of Att-supporting
confidence: 92%
“…3A). The TGN region of sh-1A PAM-1 cells is vacuolated; noncondensing secretory granules accumulate at the expense of immature secretory granules, and secretagogue-stimulated secretion is diminished (7). Although decreased expression of 1A resulted in lower levels of another AP-1 subunit (␥-adaptin), we confirmed that levels of ␣-adaptin, an AP-2 subunit, were unaffected (Fig.…”
Section: Atp7a Ap-1 and Pam Co-localize In The Golgi Region Of Att-supporting
confidence: 74%
See 3 more Smart Citations